Health care quality and ethical principles - D’Empaire, Gabriel (Acta Bioethica, 2010)
Health care quality has become a fundamental requirement for any health care service. Despite the extraordinary scientific-technological development achieved in the last decades, the complexity of health care services provokes the increase of medical errors with very negative consequences in morbidity, mortality and health care costs. Several health care quality models have been raised. Nevertheless, in general these are implemented as administrative, management processes far from the actual work of staff which must use them. Health care quality must not be perceived only as medical management problem, but as an ethical problem and, as such, it must be based on education on values which guarantee active participation of all stakeholders, being excellence, solidarity and professionalism fundamental values.